Traditional Chinese Medicine nursing of a patient with postoperative pain after surgery for breast cancer (1例乳腺癌患者术后疼痛的中医状态调护) - CHEN Hong (陈宏); DENG Jianhua (邓建华); LI Suqian (李苏茜); ZHOU Jie (周洁); LI Ye (李野); E Haiyan (鄂海燕); ZHENG Ping (郑萍); TANG Ling (唐玲) (中西医结合护理)
This paper summarized the Traditional Chinese Medicine (TCM) nursing of a patient with postoperative pain after surgery for breast cancer. The patient had received a comprehensive nursing assessment after hospital admission. Based on the TCM syndrome differentiation, appropriate technique of TCM nursing including TCM ointment massage, cupping therapy, TCM medication and emotional care were carried out to relieve the negative emotion and postoperative pain of the patient. (本文总结1例乳腺癌患者术后疼痛的中医状态调护经验。患者入院后完善护理评估, 基于中医辨证, 采取中药膏摩、拔罐疗法、口服中药、情志护理等中医护理适宜技术干预, 有效改善患者负性情绪, 减轻疼痛, 有助于提高肿瘤患者生存质量。)